Assessing Standard English in 4.0 Era: Teacher’s Perceptions on the Effectiveness of Kahoot! and Quizizz in English Classroom - Shella Gherina Saptiany; Januarius Mujiyanto; Rudi Hartono; Katharina Rustipa (Universitas Negeri Semarang, 2022)
Abstrak. Standard English is the variant of English that is commonly used as a world language, with some minor regional and national variances. Kahoot! and Quizziz are the application of game-based that is used in assessing students’ learning. The purpose of this study is to identify teacher’s perceptions on the effectiveness and obstacle in using Kahoot! and Quizziz in assessing Standard English in the classroom. This research involved an English teacher who had 15 years of teaching experience in English Foreign Language (EFL) teaching. The present study conducted an in-depth semi-structured interview for the data collection. The results indicate that there are advantages and an obstacle in using the apps. The first result is that Kahoot! and Quizziz can increase students’ motivation as they become more active in the class after the teacher gave those game-based applications to assess reading skill in Standard English. The second result is both Kahoot! and Quizziz encourages students’ participation in the class. Furthermore, Kahoot! and Quizziz ease the teachers’ work in making the questions and correcting the students’ answers. Additionally, the willingness of the students to learn English increases since teacher use digital games. Moreover, the teacher can manage the time when using Kahoot! and Quizziz, so it will be more flexible to use. The last result is the obstacle of using both Kahoot! and Quizziz that difficult to get a permit to use the mobile phone at the school.